Late Iron Age and Roman settlement at Bozeat Quarry, Northamptonshire : excavations 1995-2016 - Atkins, Rob, 1968- (Archaeopress Publishing Ltd, 2018)
MOLA (formerly Northamptonshire Archaeology), has undertaken intermittent archaeological work within Bozeat Quarry over a 20-year period from 1995-2016 covering an area of 59ha. This volume presents their findings.